An analysis of the interpersonal meaning of lyric and video “zombie” by day6 - Antari, Ni Kadek Dwi (Journal of Language and Pragmatics Studies, 2022)
Song is a learning media that often use to learn English by the students but sometimes they do not understand the meaning of the song used. This study focuses on analyze the intended meaning from some figurative expressions through the song lyric and the symbolic signs and gestures on the video clip of Day6 “Zombie”. The data of this study were the lyrics of Day6 “Zombie (English Version)” and the official video that uploaded on 11th May 2021 by JYP Entertainment. The lyrics and the video were analyzed by Fairclough’s critical discourse analysis by categorizing the figurative expressions that showed the intended meaning and explain the symbolic expressions through semiotic study. The result shows if there are six figurative expressions such as metaphor, personification, paradox, repetition, metonymy, and symbolism. The images are delivered through colour schemes, symbolic objects, and gestures. This study concluded that the intended meaning from lyrics and the music video of Day6 “Zombie” tells about the hopeless feeling of someone who always does the same thing every day.